THE NIGERIAN’S LAND TENURE POLICY AND POVERTY AMONG PEASANT FARMERS: A CASE OF HUMAN RIGHTS VIOLATION? - Orji, K.O; Omenma, J.T (University of Nigeria Journal of Political Economy, 2022)
Under customary law, elders and family heads are the dominant land owners through whom members of the community obtain access to resources via ownership, sharecropping, tenancy and pledging. Nigeria, like any other African nation inherited tenure laws from colonial government and at independence state ownership became the norm, and land was then either sold or leased privately. Thus, customary land tenure practices which bestowed land rights on peasant farmers were weakened, and politics became the basis of land distribution and acquisition. This Legal provision over land is a violation of individual and group rights, as the right to land represents a whole bundle of other rights such as the right to employment, right income and fruits from the land, right to transfer the land to other exchange for other assets (loan), right to communal citizenship and right to political power. This threatens over 90 percent peasant farmers to whom land is not only a means of livelihood, but also a source of identity and ancestral relationship. This study, therefore, intends to establish whether there is any significant link between land access, tenure security and cyclical poverty among peasant farmers in Nigeria.